Virtual Reality Simulation in Nontechnical Skills Training for Healthcare Professionals: A Systematic Review - Bracq, Marie-Stéphanie; Michinov, Estelle; Jannin, Pierre (Simulation in healthcare : journal of the Society for Medical Simulation, 2019)
This systematic review, conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, is aimed to review current research in virtual reality (VR) for healthcare training, specifically pertaining to nontechnical skills. PsycInfo and Medline databases were queried for relevant articles published through December 2017. Of the 1377 publications identified, 80 were assessed for eligibility and 26 were finally included in the qualitative synthesis. Overall, the use of virtual training for nontechnical skills is recent in healthcare education and has increased since 2010. Screen-based VR simulators or virtual worlds are the most frequently used systems. The nontechnical skills addressed in VR simulation include mainly teamwork, communication, and situation awareness. Most studies evaluate the usability and acceptability of VR simulation, and few studies have measured the effects of VR simulation on nontechnical skills development.